Razões de punir e as lacunas no retributivismo - Santos, Paulo Vinícius Borges (Universidade do Vale do Rio dos Sinos, 2023)
It is intended to analyze, in this thesis, the reasons for punishing under the prism of retributivism, highlighting its central characteristics and, above all, its gaps, as pointed out by utilitarianism (preventivist), by negative retributivism and by restitutivism. We will study, especially, the thought of Kant, Moore and Kershnar about the theory of punishment, as representatives of retributivism and Bentham, Hart and Boonin, as representatives of utilitarianism, negative retributivism and restitutivism, respectively. To do so, observe the philosophical thinking in the conceptualization of the purpose of punishment and the reasons why it should be punished. The objective is, therefore, to examine the theories of punishment in order to find answers to the questions: what justifies the general practice of punishment? Who can be punished? How can we punish? What are the shortcomings of retributivism? The research is eminently bibliographical, developed from the identification, reading, analysis and interpretation of the writings of consecrated scholars of the theory of punishment. Utilitarianism projects the function of punishment into the future, aiming at preventing new crimes. From another perspective, retributivism, when seeing the penalty as a consequence of the crime, turns its vision to the past, pointing out as its foundation the merit and punishment of the offender. And restitutivism, in which the State must force people who break the law to compensate their victims for the damage they wrongly caused. We will argue that such theories should complement retributivism, given the complexity of the institute of punishment and, thus, the reason for punishing should be constituted in a mixed and balanced system, which includes retribution to the offender for the evil committed, the prevention of new crimes and the restitution for harm caused, taking into account the legal asset protected in the specific case.
Keywords: Crime; Punição; Kant; Moore; Kershnar; Boonin; Hart; Punishment; ACCNPQ::Ciências Humanas::Filosofia